Promoting collaborative dementia care via online interprofessional education - Cartwright, J.; Franklin, D.; Forman, Dawn; Freegard, H. (2015)
Aim: This study aimed to develop, implement and evaluate an online interprofessional education (IPE) dementia case study for health science students. The IPE initiative aimed to develop collaborative interprofessional capabilities and client-centred mindsets that underpin high-quality dementia care. Method: A mixed methods research design was used to assess students' values, attitudes and learning outcomes using an interprofessional socialization and valuing scale (ISVS) completed pre and post the online case study and via thematic analysis of free text responses. Results: Students' ISVS scores improved significantly following online participation, and the qualitative results support a shift towards interprofessional collaboration and client-centred care. Conclusions: This online IPE case study was successful in developing the collaborative mindsets and interprofessional capabilities required by a future workforce to meet the complex, client-centred needs of people living with dementia.